Skarga nadzwyczajna w postępowaniu cywilnym – wybrane zagadnienia - Bartosz Wyżykowski (Studia Prawa Publicznego, 2018)
On the 3rd April 2018, a new Act of the 8th December 2017 regarding the Supreme Court (Journal of Laws 2018 item 5 as amended), hereinafter the “Law regarding the Supreme Court”, entered into force, which introduced to the polish legal system a new institution, namely the extraordinary complaint. It is a new remedy, the purpose of which is the extraordinary review of final court decisions (judgements) in order to ensure their compliance with the principle of a democratic state of law that implements the principles of social justice. It may be brought before the Supreme Court only by certain public authorities strictly specified in the Law regarding the Supreme Court, namely by the Attorney General and the Ombudsman but also, within the scope of their jurisdiction, inter alia by the Financial Ombudsman, the Small and Medium-sized Enterprises Ombudsman and the President of the Office for Competition and Consumer Protection. Thus, these entities were given the right to challenge final judgments of common courts, which otherwise could not be revoked or changed by any other means or remedies. Currently, all legitimized authorities may file extraordinary complaints – with the reservation that authorities other than the Attorney General and the Ombudsman may do so only within their jurisdiction – regarding judgments that became final after the 3rd April 2018 (inclusive). However, the Attorney General and the Ombudsman may also, until the 3rd April 2021, file extraordinary complaints regarding judgments that became final after the 17th October 1997 and before the 3rd April 2018 (the date the Law regarding the Supreme Court entered into force). Aim of the article is to analyze the main legal issues regarding the extraordinary complaint, especially the grounds for its admissibility, the practical aspects in the subject matter, as well as possible disputable issues and interpretation doubts. The study is limited to the analysis of selected legal issues regarding the extraordinary complaint in the civil procedure.